d30Si signatures (%) of surface sediments off Peru - Kristin Doering; Claudia Ehlert; Patricia Grasse; Xavier Crosta; Sophie Fleury; Martin Frank; Ralph R Schneider (PANGAEA, 2021)
The dataset comprises all d30Si signatures (bSiO2 and Coscinodiscus) of surface sediments off Peru